PERANAN KEPOLISIAN SATUAN LALU LINTAS DALAM PENINGKATAN DISIPLIN BERLALU LINTAS TERHADAP PENGEMUDI KENDARAAN BERMOTOR DI WILAYAH HUKUM KEPOLISIAN RESOR DUMAI - Harahap, Ogy Ramajuary At; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Each person uses a motor vehicle to facilitate its activities to mobilize or move from one place to another in everyday life, whether it was a two-wheeler or four-wheeled vehicles. As motorists must give priority to safety and obey the rules that apply in accordance with applicable regulations in the State Indonesia. Pursuant to Article 106 paragraph (4) (a) of Law Number 22 Year 2009 regarding Traffic and Road Transportation. The research objective of this thesis, namely; First, to determine the role of Police Traffic Unit Dumai, second, to determine the factors that influence the legal awareness in traffic in Dumai Police Jurisdiction, Third, To know the efforts made by the Police Traffic Unit Dumai.This type of research can be classified into types yiridis sociological research. This research was conducted at the Police Traffic Unit Dumai, the data source used, primary data, secondary data, and the data tertiary, data collection techniques in this study with interviews, questionnaires, observation, literature study, and data analysis.From the research problem there are three basic things that can be inferred. First, the role of the Unit of Traffic Police Dumai in increasing traffic discipline against motorists, there are a few roles are performed, first, the role of the field of prevention, namely by way of socialization or counseling and information about signs traffic to school-school and community, Second, the field of repressive role, namely to take actions to give warning to offenders who are not too fatal and prosecution by giving him a ticket for violators were fatal. Second, the factors that influence the legal awareness in traffic in Dumai Police Jurisdiction, namely law enforcement factor, factor means or facilities, community factors. Third, efforts made by the Police Traffic Unit Dumai to overcome the obstacles that is, increase the number of personnel, giving instruction to members of Traffic, propose an increase in funding and facilities and amenities to the leadership, increase socialization schedule of traffic rules. Suggestions Author, First, the increase in traffic discipline need to be improved work patterns, Second, increase the budget, facilities, amenities, as well as the number of personnel, third, in increasing public awareness need socialization and counseling about traffic rules to the public. Keywords: Role - Traffic Unit - Motor Vehicle Drivers